2021
DOI: 10.3390/s21072430
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Forecasting of Univariate Agrometeorological Data: A Comparative Performance Evaluation via One-Step and Multi-Step Ahead Forecasting Strategies

Abstract: High-frequency monitoring of agrometeorological parameters is quintessential in the domain of Precision Agriculture (PA), where timeliness of collected observations and the ability to generate ahead-of-time predictions can substantially impact the crop yield. In this context, state-of-the-art internet-of-things (IoT)-based sensing platforms are often employed to generate, pre-process and assimilate real-time data from heterogeneous sensors and streaming data sources. Simultaneously, Time-Series Forecasting Alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 57 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Sahoo et al [19] also demonstrated the superiority of LSTM over RNN on univariate daily discharge data from the Basantapur gauging station in India's Mahanadi River basin. Suradhaniwar et al [7] demonstrated that SARIMA and SVR models outperform NN, LSTM, and RNN models when hourly averaged univariate time series data is used. Even though the best model generalization is complex, case-based analysis is the most effective method for determining which model best fits a given situation [60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sahoo et al [19] also demonstrated the superiority of LSTM over RNN on univariate daily discharge data from the Basantapur gauging station in India's Mahanadi River basin. Suradhaniwar et al [7] demonstrated that SARIMA and SVR models outperform NN, LSTM, and RNN models when hourly averaged univariate time series data is used. Even though the best model generalization is complex, case-based analysis is the most effective method for determining which model best fits a given situation [60].…”
Section: Resultsmentioning
confidence: 99%
“…Univariate forecasting models are straightforward to train using sparse data and provide ease of inference when evaluating forecast performance. Due to the complexity of agrometeorological data, it is simpler and more efficient to forecast the variables individually [7]. On the other hand, multivariate models are designed with multiple variables such as precipitation, temperature, evaporation, and other variables as input and a streamflow variable as output [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also differs from classical approaches based on sliding windows and thresholds of statistical moments [3]. [1,4,16,32], [1,2,4,8,16,32], [1,3,6,12,24], [1,2,6,12,24], [1,2,4,8,16], [1,4,16], [1,2,4,8], [1,4,8] Blocks 1, 2 Dropout 0…”
Section: Osts Methodsmentioning
confidence: 99%
“…Time series are explored in several types of applications and but not the subject of study until today. Most of these applications are focused on forecasting [32,33] and feature extraction [5] approaches, as can be seen in the following studies.…”
Section: Related Workmentioning
confidence: 99%